(untitled) (Riwayat: Educational Journal of History and Humanities, 2026)
This study has the aim of implementing financial statements that are in accordance with the financial accounting standards of private entities (SAK-EP) at PT Alfath Corporation Malang City. The background of the research is based on the existence of the accounting gap phenomenon in creative technology companies that still use simple recording and have not met official accounting standards, so that it can inhibit access to funding and credibility on businesses. The method used is descriptive qualitative methods with a focus on practical implementation of new accounting standards. Data is collected through the company’s financial transaction observation and documentation in a certain period, such as salary data, marketing costs and permanent asset purchases. The analysis was carried out by compiling the accounting cycle ranging from general journals to the presentation of financial statements that were obedient to the standard of SAK-EP. The results showed that the application of SAK-EP at PT Alfath Corporation allowed the company to present more transparent and more accurate financial statements, especially in reflecting the fair value of acet-based assets and recognition. This implementation provides a strong basis for management in strategic decision making and increasing the trust of external parties companies such as banks and prospective investors. Although there are challenges in the transition from the old system, 100% compliance with SAK-EP can sauce to carry out the sustainability of the company in the creative technology sector.